Debt Transfer A Jurisprudential Study (Fatwa of the Council of Indonesian Scholars as a Model) - Muqorobin, Ahmad; Elsefy, Hossam El-Din (International Journal of Al-Turath In Islamic Wealth and Finance, 2023)
In his commercial or other dealings, a person needs to borrow from several people, and lend to others, so at the same time, he is a creditor and a debtor. A person must fulfill the right of his debtor himself, and then pay it back to his creditor. On the other hand, recent phenomena have emerged from bank customers who wish to transfer their debts from conventional banks to Islamic banks, in order to keep them away from usurious interests, so it is easy to waive these obligations, except through debt transfer. This research aims to study jurisprudence in the implementation of the debt transfer contract in Indonesian Islamic banks in view of the fatwa issued by the Council of Scholars of Indonesia. This research relies on the descriptive approach in determining the nature of debt transfer assignment, and the inductive analytical approach in analyzing the fatwa on debt transfer at the Indonesian Council of Scholars and its forms applied in Islamic banks or financial institutions, with linking it to jurisprudential conditioning and presenting and answering the problems in it. This research obtains several results, which are that Fatwa on Debt Transfer No. 31/DSN-MUI/VI/2002, which contains copies of the contracts applied in Islamic banks are: (1) The contract of loan and sale with a form of Murabahah, (2) The contract of co-ownership and sale with a form of Murabahah, (3) The loan and lease contract, (4) The loan and lease contract ending with ownership. And the jurisprudential analysis in those previous contracts, which is that Islamic banks and financial institutions must pay attention in applying the transfer of debt to falling into usurious transactions such as selling the sample, and also in the loan contract that no payment or increase comes from it, so the value of the wage is provided by the benefit from the work.